(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
In this article, the representation of childhood in Delia Domínguez’s poetry is analyzed. This is expressed as an aesthetics of orfhanhood and bastardy (huachismo) that tries to return to an original, embryonic condition, by means of a constant looking back through a girl’s eyes, in the context of a poeticized community that gives way to the regressive and impossible meeting of a mother and her daughter. In this search, childhood fulfills a reunifying and repairing role.